Acidic dynamics: Unveiling mechanistic insights for improved performance in chitosan triboelectric nanogenerators - Charoonsuk, Thitirat; Ukasi, Sirinya; Mokthaisong, Panadta; Khuntakaew, Pawita; Hajra, Sugato; Kim, Hoe Joon; Muanghlua, Rangson; Vittayakorn, Wanwilai; Pongampai, Satana; Vittayakorn, Naratip (My University, 2024)
In recent years, there has been a surge in interest surrounding the development of chitosan (CS)-based triboelectric nanogenerators (TENG) for powering attachable/portable devices. Despite numerous strategies aimed at enhancing their efficiency, the selection of acid solvent has remained largely unexplored. In this study, various acids, including acetic (CH3COOH), succinic (C4H6O4), and citric (C6H8O7) acids, were investigated for their impact on mechanical and electrical output signals. Remarkably, the choice and concentration of acid were found to significantly influence performance. Specifically, employing citric acid rendered the CS solid film more pliable and yielded the highest output signal at optimal concentration levels. Under optimized conditions, the CS-TENG exhibited an open-circuit voltage output (VOC) of 157 V and short-circuit current output (ISC) of 53 µA—more than triple that of pristine CS-TENG. Mechanistic insights into electrical generation have been elucidated, underscoring the importance of solvent selection in CS TENG fabrication. These findings underscore the potential for tailored acid solvent selection to advance specialized applications in the field.
Keywords: carboxylic acids; Chitosan; triboelectric nanogenerator